Responding to Environmental Issues through Adaptive Collaborative Management: From Forest Communities to Global Actors - Pierce Colfer, Carol J.; Prabhu, Ravi (Routledge, 2023)
Focused on forest management and governance, this book examines two decades of experience with Adaptive Collaborative Management (ACM), assessing both its uses and improvements needed to address global environmental issues.